IMPACTS OF CHATBOTS ON THE ACCOUNTING SERVICE INDUSTRY - Dan Marius Coman; Violeta State; Maria Cristina Voinea; Gabriel Cucui (Agora International Journal of Economical Sciences (AIJES), 2023)
The integration of chatbots into the accounting services industry has become increasingly popular, and their adoption rates are expected to almost double in the next two to five years. Chatbots can automate routine tasks, allowing accountants to focus on more complex and client-oriented work, and AI-powered chatbots can provide more accurate data entry and reduce the time spent on manual tasks. However, their successful implementation requires consideration of a range of challenges. These include integration with existing systems and processes, data privacy and security concerns, ensuring accuracy and consistency in responses, and managing customer expectations and trust. The financial industry is increasingly turning to the use of chatbots for customer support and sales. The global conversational AI market is expected to grow significantly in the coming years. The analysis of the answers given by ChatGPT highlights both positive aspects: the generation of acceptable answers to questions of a theoretical nature; compiling information very well from various available information sources; providing answers to all questions asked; as well as negative aspects: making erroneous calculations when asked to solve practical problems that require a selection of information from different sources available; the elaboration of correct but incomplete answers for the cases in accounting; and the use of this tool in accounting.
Keywords: 330